Blackwell handbook of judgment and decision making / edited by Derek J. Koehler and Nigel Harvey. - Koehler, Derek J.; Harvey, Nigel. (Handbooks of experimental psychology., 2004)
"The Blackwell Handbook of Judgment and Decision Making is an overview of current topics and research in the study of how people make evaluations, draw inferences, and make decisions under conditions of uncertainty and conflict. Chapters are contributed by experts in the field from various disciplines such as psychology, cognitive science, business, and law. The selection of topics reflects current trends and controversies in judgment and decision-making research. Each chapter provides an overview of important past research and a report on current research and future directions in various areas in the study of human judgment and decision making."--Jacket.